COMPARISON OF INCOME AND STAPLE FOOD AVAILABILITY OF RAWA LEBAK RICE FARMING HOUSEHOLDS BASED ON LAND TYPOLOGY IN KALIDONI DISTRICT, PALEMBANG CITY - Silvian, Trissa; Yunita; Iqbal, Muhammad (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Lebak swamp land is a type of suboptimal land with high potential for the development of national rice production, although it is highly influenced by climatic conditions and the typology of water inundation. Variations in lebak swamp land typology lead to differences in productivity, as well as in household farmers' income levels and food availability. This study aims to analyze household income sources and staple food availability among rice farmers based on the typology of lebak swamp lands (shallow, middle, and deep) in Sei Selincah Subdistrict, Kalidoni District, Palembang City. A survey method was employed using proportional stratified random sampling, involving 60 respondents. Data were analyzed quantitatively to calculate income, expenditure, and food availability. The results showed that the highest income was earned by farmers in deep swamps (IDR 27,832,049/year), followed by middle swamps (IDR 26,221,862/year), and shallow swamps (IDR 24,609,383/year). Non-agricultural income significantly contributed to household finances, particularly in shallow and middle areas. Non-rice farming activities, such as galangal cultivation, were only practiced in shallow and middle swamps. Household expenditures were primarily allocated to non-food needs, especially education and savings. Meanwhile, household food availability remains low and varies across land typologies. The highest food availability is found in the middle swamp at 443 kg/year, followed by the deep swamp at 425 kg/year, and the shallow swamp at 405 kg/year. Most of the surplus is sold to meet other household needs. These findings highlight the importance of income diversification and improving food storage capacity to enhance the economic and food security of lebak swamp rice farmers. Keywords: farmer welfare, food availability, household expenditure, household income, lebak swamp